(3GdTGaj aj TQM eSfO GdTGaYis - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s; (3CHh YHO Gddg eMeO Hf GOQjS GdTGaYjs
(3ChdgG (B:s
(3jHOC HGdaUd GdKGfi ai GdejbGJ GdecGfi hajg aQYGf GdaQY GdChd ai ejbGJ GdML s
(3BNQgG (B:s
(3jfJgi HGdHGH GdKGdK YTQ ai PcQ GdMQejf s
(3GdfSNI HgG MhGTs
(3cJHJ GdYfGhjjf HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdMOjK h GdeUWdMs